2017
DOI: 10.1097/scs.0000000000003182
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Deformity in Long-Standing, Untreated Congenital Muscular Torticollis

Abstract: There were seemingly permanent changes along the cervical spine region in the adult patients with long-standing, untreated CMT in the form of bending and rotation deformities that might result in residual torticollis postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…We believe that young patients have a greater potential for remodeling the scoliosis after surgery and long-standing cases may progress toward a fixed deformity. Using three-dimensional computed tomography, Hussein et al2) demonstrated that there were definitive vertebral deformities along the cervical spine in long-standing patients with CMT. Therefore, we suggest that it may be better to perform surgery for patients with CMT and scoliosis when growth potential remains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We believe that young patients have a greater potential for remodeling the scoliosis after surgery and long-standing cases may progress toward a fixed deformity. Using three-dimensional computed tomography, Hussein et al2) demonstrated that there were definitive vertebral deformities along the cervical spine in long-standing patients with CMT. Therefore, we suggest that it may be better to perform surgery for patients with CMT and scoliosis when growth potential remains.…”
Section: Discussionmentioning
confidence: 99%
“…Torticollis is derived from a Latin word meaning twisted neck 12). Congenital muscular torticollis (CMT) is one of the most common types of this condition and is caused by fibromatous contracture of the sternocleidomastoid (SCM) muscle 234). It usually presents with a hard mass within the affected SCM muscle in the neonatal period 1356).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…From the above process, patients with congenital torticollis were divided into the following four groups: ocular torticollis, defined as torticollis caused by ophthalmic conditions, such as disorders of ocular movement and nystagmus [ 10 , 11 ]; neurogenic torticollis, defined as abnormal head and neck posture due to associated neurologic abnormalities that weakens the neural connections required for proper head and neck positioning (e.g., cerebral palsy) [ 11 , 12 ]; osseous torticollis, defined as torticollis associated with congenital malformation of the spine such as vertebral segmentation defects [ 11 , 13 , 14 , 15 ]; and CMT, diagnosed by evidence of shortening of the SCM muscle via physical examination and/or enlarged thickness, heterogeneous echogenicity, fibromatous lesion, or asymmetry of the SCM muscle on sonographic findings. The diagnosis of CMT included tumor, muscular, and postural types [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%